PENGELOLAAN KANDUNGAN BAHAN ORGANIK PADA LIMBAH CAIR LABORATORIUM PROLINGMSP-IPB DENGAN BERBAGAI KOMBINASI AGEN BIOREMEDIASI - Pratiwi, Niken Tunjung Murti; Hariyadi, Sigid; Ayu, Inna Puspa; Apriadi, Tri; Iswantari, Aliati; Wulandari, Dwi Yuni (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACT Wastewater from laboratory glassware washing activities contains organic materials. Decomposing bacteria could increase the biomass by utilizing organic matter as a source of carbon. This research was aimed to describe the influence of commercial probiotic application in reducing organic matter content of Proling laboratory wastewater. The research was conducted from February to July 2016 in Aquatic Microbiology Laboratory. The experiment consists of several treatments, those were wastewater (L), wastewater+molase (LM), and wastewater+molase+bacteria from commercial probiotic (LMB). Major parameters observed were COD and bacteria abundance. The results showed that there was significant response difference between molasses and without molasses treatment. Based on COD, the most influenced treatment in decreasing organic matter were LM and LMB. These treatments could decrease COD up to 97% and 91%. Furthermore, the abundance of bacteria in molasses treatment was higher than without molasses. Based on this study, the most effective treatment in reducing organic matter was LMB.  Keywords: bacteria, laboratory wastewater, molasses, organic matter